Decision support systems - Janakiraman, V.S.; Surakest, K. ([S.l.] : Prentice-Hall of India Pvt.Ltd, 2004)
Designed as a textbook for students of computer science, computer applications, management, and information technology, this book deals with the subject in an orderly manner and will be useful to all thoese engaged in designing practical systems.
Keywords: Decision support systems; Decision support systems